Assessment of Nutrition and Supplementation in Patients With Hip Fractures - James Arkley; Ján Dixon; Faye Wilson MBBS, MSC; Karl Charlton MRES; Benjamin John Ollivere; William Eardley MD, FRCSEd (Tr&Orth) (Geriatric Orthopaedic Surgery & Rehabilitation, 2019)
Introduction: Malnutrition is common in older people, is known to interact with frailty, and is a risk factor for wound complications and poor functional outcomes postoperatively. Sustaining a hip fracture is a significant life event, often resulting in a decline in mobility and functional ability. A poor nutritional state may further impede recovery and rehabilitation, so strategies to improve perioperative nutrition are of considerable importance. We provide a review of nutritional supplement practices in this vulnerable and growing population. Method: Systematic review of preoperative oral nutritional supplementation (ONS) in hip fracture patients. Results: We identified 12 articles pertaining to this important area of perioperative care. The findings suggest postoperative ONS can improve postoperative outcomes in hip fracture patients, especially in terms of increasing total serum protein, improving nutritional status to near-optimum levels, and decreasing postoperative complications. Discussion: There is an absence of evidence specific to preoperative ONS in patients admitted following hip fracture. Literature relating to other populations is encouraging but is yet to be robustly studied. It is unclear whether these results are generalizable to the frailer hip fracture population. There is a need for studies clearly defining outcome measurement and complication assessment pertaining to preoperative ONS. The potential benefit is considerable, and this review will provide a means to inform the construction of meaningful trials in preoperative ONS of patients sustaining hip fracture. Conclusion: Oral nutritional supplementation in hip fracture patients may decrease postoperative complications while increasing elderly patient’s nutritional state to a near-optimum level. This is extrapolated from postoperative literature, however with a clear gap in research pertaining specifically to preoperative care. The need for well-constructed studies focused on the impact and assessment of early ONS in this population is transparent.